French labour legislation: points (note) - A. C.
013-0086-001 FRENCH LABOUR LEGISLATION: POINTS. 1. Find out whether in the law of June 1936, on the 40-hour week, there was any provision made for the rate of pay for overtime. For instance, metalworkers' collective agreements contained a clause for time-and-a-quarter for the first two hours' overtime, and time-and-a-half for subsequent overtime. 2. French Governments since Léon BLUM, and the dates on which they came into power. Extra copy of "Industrial & Labour Information" for 18th September, 1939, and for 11th December, 1939. A.C. 3.4.40 292/946/13/86